Intra-Articular Biocompatibility of Multistranded, Long-Chain Polyethylene Suture Tape in a Canine ACL Model - Smith, Patrick A.; Bozynski, Chantelle C.; Kuroki, Keiichi; Henrich, Sarah M.; Wijdicks, Coen A.; Cook, James L. (The Journal of Knee Surgery, 2019)
The purpose of this study was to assess intra-articular use of a nonabsorbable braided suture tape for its biocompatibility when implanted adjacent to the native anterior cruciate ligament (ACL) in a canine model. Establishing biocompatibility of suture tape in the knee is an important foundational step for clinicians considering use of suture tape augmentation for ACL reconstruction or repair. The study hypothesis was that a nonabsorbable braided suture tape would be biocompatible in the knee with no resultant adverse functional consequences, and no significant intra-articular synovial reactions or articular cartilage degeneration attributable to direct exposure to the suture tape, whether intact or transected. Nonabsorbable braided suture tape was arthroscopically implanted adjacent to the native ACL of dogs (n = 6). The suture was intact in half of the dogs and was transected in the other half as a “worst-case” scenario. Dogs were assessed for postoperative complications and morbidity. Arthroscopic grading of synovium and cartilage was performed at 4 and 6 months. Histologic assessments were performed at the 6-month endpoint and compared with the ACL partial tear (n = 9) and ACL reconstruction (n = 5) cohorts as well as historical sham controls. No postoperative complications were noted. No animal developed lameness or clinical dysfunction, and there were no severe inflammatory or immune responses, cartilage erosions, or premature osteoarthritis noted. Arthroscopic assessments revealed no to mild synovitis and no apparent cartilage damage in either group. Histologically, both the intact and transected suture tape groups were associated with significantly (p ≤ 0.05) less synovial and articular cartilage pathology compared with the partial ACL transection and patellar bone–tendon–bone ACL autograft reconstruction cohorts, and matched historical sham controls. The hypothesis was accepted as study results support the biocompatibility of suture tape in the canine knee.
Keywords: anterior cruciate ligament; suture tape; FiberTape; internal bracing; biocompatibility